2019
DOI: 10.1080/0966369x.2019.1640188
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal masculinities: seasonal labor migration and masculinities in rural western India

Abstract: In this research article, I study seasonal labor migration in rural western India to understand gender negotiations in the course of labor migration. Based on qualitative research conducted in six villages in rural Maharashtra state in Western India during the early Kharif cropping season in 2014 and during Kharif and Rabi cropping seasons in 2015-16, I examine gendered labor in migrant home communities and at various rural and urban employment destinations, the relationship of labor to the social construction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 42 publications
0
13
0
Order By: Relevance
“…Non-agricultural activities without a labor contract performed in countries with the transitional economy contribute between 20-70% to workers' real income (Mishra, 2018). In other words, to make ends meet, informal workers in rural areas, apart from working in agriculture, are also engaged in different industries' production, business, and services (Rahe and Hause, 2020;Rai, 2020). Besides, to the money amount achieved by workers' participation in the labor market, they also receive income from property leases, government subsidies, and support from family, relatives, etc.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Non-agricultural activities without a labor contract performed in countries with the transitional economy contribute between 20-70% to workers' real income (Mishra, 2018). In other words, to make ends meet, informal workers in rural areas, apart from working in agriculture, are also engaged in different industries' production, business, and services (Rahe and Hause, 2020;Rai, 2020). Besides, to the money amount achieved by workers' participation in the labor market, they also receive income from property leases, government subsidies, and support from family, relatives, etc.…”
Section: Literature Reviewmentioning
confidence: 99%
“…This research is part of a larger project to examine labor migration and social change in rural western India (Rai, 2013, 2018a, 2018b, 2019; Rai and Smucker, 2016). In Yavatmal district, I interviewed all the truckers and Muqaddams in five villages, and I conducted a focus-group discussion with truckers and Muqaddams in the sixth village.…”
Section: Cane Labor Migration In Maharashtramentioning
confidence: 99%
“…Studies of Deshingkar and Daniel (2003), Islam et al (2019), Keshri and Bhagat (2010), Khatun and Roy (2016), Rafique (2003), Rai (2020), Rogaly and Coppard (2003) and Rogaly et al (2001) have shown the importance of seasonal migration in livelihood strategies of the SEBLP in rural areas and has been increasingly becoming an accumulative alternative for them. Numerous studies (Debnath, 2020;Garikipati, 2008;Ghosh and Mal, 2017;Keshri and Bhagat, 2010;Keshri and Bhagat, 2012;Rademacher-Schulz et al, 2014;Rafique, 2003;Rogaly and Coppard, 2003;Rogaly et al, 2001) have pointed out several factors of seasonal migration, where job opportunities and poverty are the primary reasons behind seasonal migration.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In India, seasonal migration of agricultural labourers is an essential process among SEBLP for their survival in the slack season (De Haan, Brock & Coulibaly, 2002;Keshri and Bhagat, 2013;Singh et al, 2011;Sundari, 2005). Their mobility is linked either directly or indirectly with the seasonal trough in the agricultural production cycle of the home region (Agarwal, 1990;Beck, 1989) and it follows the rhythm of crop harvest cycles in migrant destinations and home villages (Rai, 2020). Uttar Pradesh, Maharashtra, Bihar, West Bengal, Orissa are the dominant states of seasonal migration where young rural people used to migrate during the season of crop harvesting and sowing with least women participation (Rai, 2020;Thapa and Yadav, 2015).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation